Knowledge and awareness on depression of hospitalised elderly patients among nurses in HUSM - Yuyud, Putri Norfitria Nurulaspy Asep (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
The median prevalence of depressive disorders among older persons from 74 studies with a total of 487 275 older people was 10.3% worldwide. Depression is among the most common mental disorders in older people. Nurses are the key practitioners in health care that provide elderly patients with direct care. Nurses' experience and attitudes appear to have an impact on their ability to work with older people and the quality of care they provide. A cross-sectional study was carried out to study the knowledge and awareness on depression of hospitalised elderly patients among nurses in Hospital Universiti Sains Malaysia. 239 nurses from Hospital USM who met the inclusion criteria were recruited. Nurses’ level of knowledge and awareness were measured by using the Late Life Depression Questionnaire and Pullen Symptom Quiz developed in previous study with adequate reliability. The questionnaire comprised of three parts; sociodemographic data, nurses’ level of knowledge, and nurses’ level of awareness. Higher scores indicate better level of knowledge and awareness. Most of the respondents were female (87.4%) with the majority in age group between 31 and 40 (51.0%). Among the respondents, 37.7% were nurses who had working experience between 6 to 12 years, which was the majority. The study reported that the nurses had poor knowledge (74.9%) regarding depression among elderly patients, while they scored average (68.2%) for the awareness on early signs of depression among elderly. Pearson’s correlation was used to determine the relationship between knowledge score and awareness score. There was a positive significant relationship between the two variables (r = 0.146; P = 0.024). There is no statistically significant correlation between working experience and the level of knowledge of nurses in Hospital USM (r = 0.001; P = 0.988). Nurses’ knowledge and awareness regarding depression and its early signs among elderly patients were at a poor and average level, respectively. This part can be improved by introducing depression assessment protocols and well-structured continuing education programs.